Human Capital Mobility: Implications for Efficiency, Income Distribution, and Policy - David E. Wildasin (Center for Economic Studies and ifo Institute (CESifo), 2014)
Mobility of highly-skilled workers affects and is affected by labor market conditions, taxes, and other policies. This paper documents the demographic and fiscal importance of international migration, especially in aging societies, reviews the efficiency and distributional effects of mobility, and analyzes the economic incidence of fiscal transfers to low-skilled workers that are financed by taxes on imperfectly-mobile high-skilled workers in a dynamic model, distinguishing the short-run, transitional, and long-run gains and losses to contributors and beneficiaries.
Keywords: H00; 330; migration; human capital; taxation; redistribution; education